The Role of Payment Technology and Digital Marketing in Shaping Gen Z Consumer Behavior: A Literature Review and Future Research Directions - Junianto, Pilifus; Suudiah, Vina Apriliani (Sekolah Tinggi Ilmu Ekonomi Bentara Persada, 2025)
Generation Z, as digital native consumers, exhibit unique behavioral patterns in adopting digital payment technologies and responding to digital marketing strategies. This article reviews 20 reputable international journals related to the role of digital payment technology and digital marketing in shaping Generation Z's consumer behavior. Through thematic analysis, it is found that ease of use, security, and trust are the main drivers of digital payment adoption, while personalized and interactive digital marketing effectively increases purchase intentions and loyalty. The study also highlights the synergistic interaction between payment technology and digital marketing, which remains underexplored comprehensively. This article recommends longitudinal studies, integrated approaches combining technology and marketing aspects, qualitative methodologies, as well as exploration of security and cultural issues as crucial directions for future research.